2012
DOI: 10.1124/jpet.112.192047
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Inflammatory Fungal Compound (S)-Curvularin Reduces Proinflammatory Gene Expression in an In Vivo Model of Rheumatoid Arthritis

Abstract: In previous studies, we identified the fungal macrocyclic lactone (S)-curvularin (SC) as an anti-inflammatory agent using a screening system detecting inhibitors of the Janus kinase/signal transducer and activator of transcription pathway. The objective of the present study was to investigate whether SC is able to decrease proinflammatory gene expression in an in vivo model of a chronic inflammatory disease. Therefore, the effects of SC and dexamethasone were compared in the model of collagen-induced arthritis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…As shown in Fig. 5E (26). Compared with PBStreated mice we observed reduced TTP and enhanced Nox2 mRNA expression in the paws of CII-treated mice (Fig.…”
Section: Increased Nox2 Expression In Ttp-deficient Mice Correlates Wmentioning
confidence: 58%
See 1 more Smart Citation
“…As shown in Fig. 5E (26). Compared with PBStreated mice we observed reduced TTP and enhanced Nox2 mRNA expression in the paws of CII-treated mice (Fig.…”
Section: Increased Nox2 Expression In Ttp-deficient Mice Correlates Wmentioning
confidence: 58%
“…Induction of CIA and Measurement of mRNA Expression in Paws-CIA induction in V␀12-DBA/1 mice, RNA isolation, and mRNA expression analyses were performed as described (26). mRNA expression of TTP and Nox2 in paws of PBS-or chicken CII-treated animals was analyzed at day 33 after the first CII treatment.…”
Section: Methodsmentioning
confidence: 99%
“…S1A), suggesting a potential role in immune regulatory responses. Additionally, GPSM3 mRNA was recently shown to decrease in the paw after anti-inflammatory treatment with dexamethasone in the Collagen Induced Arthritis (CIA) model (7), supporting a potential role for GPSM3 in inflammatory arthritis.…”
Section: Introductionmentioning
confidence: 93%
“…The location of the Gpsm3 gene within the class III major histocompatibility class locus suggested that AGS4/Gpsm3 is expressed primarily in the immune system, and initial observations from us and others indicated this was indeed the case (Cao et al, 2004;Kimple et al, 2004;Zhao et al, 2010;Schmidt et al, 2012;GiguĂšre et al, 2013). We also discovered AGS4 expression in primary bone marrow-derived dendritic cells and splenocytes (Fig.…”
Section: Resultsmentioning
confidence: 53%